Genome‐Wide Reduction in Chromatin Accessibility and Unique Transcription Factor Footprints in Endothelial Cells and Fibroblasts in Scleroderma Skin. Issue 8 (7th July 2021) - Tsou, Pei‐Suen; Palisoc, Pamela J.; Ali, Mustafa; Khanna, Dinesh; Sawalha, Amr H.
Abstract : Objective: Systemic sclerosis (SSc) is characterized by widespread fibrosis and vascular complications. This study was undertaken to examine the chromatin landscape and transcription factor footprints in SSc, using an assay for genome‐wide chromatin accessibility. Methods: Dermal endothelial cells (ECs) and fibroblasts were isolated from healthy controls and patients with diffuse cutaneous SSc (dcSSc). Assay for transposase‐accessible chromatin with sequencing (ATAC‐seq) was performed to assess genome‐wide chromatin accessibility at a read depth of 150 million reads per sample. Transcription factor footprinting and motif binding analysis were performed, followed by functional experiments. Results: Chromatin accessibility was significantly reduced in dcSSc patients compared to healthy controls. Differentially accessible chromatin loci were enriched in pathways and gene ontologies involved in the nervous system, cell membrane projections and cilia motility, nuclear and steroid receptors, and nitric oxide. In addition, chromatin binding of transcription factors SNAI2, ETV2, and ELF1 was significantly increased in dcSSc ECs, while recruitment of RUNX1 and RUNX2 was enriched in dcSSc fibroblasts. We found significant down‐regulation of the neuronal gene NRXN1 and up‐regulation of SNAI2 and ETV2 in dcSSc ECs. In dcSSc fibroblasts, down‐regulation of the neuronal gene ENTPD1 and up‐regulation of RUNX2 were confirmed. Further functional analysis revealed that ETV2 and NRXN1 dysregulation affected angiogenesis in ECs, while ENTPD1 enhanced profibrotic properties in dcSSc fibroblasts. Conclusion: Our data identify the chromatin blueprint of dcSSc, and suggest that neuronal‐related characteristics of SSc ECs and fibroblasts could be a culprit for dysregulated angiogenesis and enhanced fibrosis. Targeting the key pathways and transcription factors identified might present novel therapeutic approaches in SSc.